Pilgrimage as a Medium: Teaching Art on the Camino de Santiago - Roxana Pérez-Méndez; Mario Marzan (Ad Limina)
Walking as a social art practice is a pedagogical tool for teaching pilgrimage, allowing students to map their experiences onto a millennia-old tradition while forming a dialogue with the expansive surrounding landscape. Liminal in form and transformative in experience, aesthetic pedestrianism and the performance of pilgrimage share many commonalities, both functioning as performative actions and as ritual reenactments of our shared human condition. This paper will present as a case study the work of artists and professors Roxana Pérez-Méndez and Mario Marzán, who utilize pilgrimage through the context of an embodied walking art practice. By viewing the Camino de Santiago as a site for creative inquiry, students on their journey become intimately tied to the creation process—part social practice, part radical healing, and part counter-mapping. The trace elements of the experience serve as a field guide on relating meaningfully to the environmental, political, or social changes of our moment.